The epidemiology of head and neck squamous cell carcinoma in The Netherlands during the era of HPV-related oropharyngeal squamous cell carcinoma. Is there really evidence for a change?. Issue 10 (October 2015) - van Monsjou, H.S.; Schaapveld, M.; van den Brekel, M.W.M.; Balm, A.J.M.
Highlights We evaluate trends in incidence of oral and oropharyngeal cancer. The incidence of oropharyngeal cancer increases. Among females, similar increases for oral tongue and cavity were found. Smoking and alcohol consumption are the main cause for developing oral and oropharyngeal cancer. Improved prognosis for oropharyngeal cancer is a result of a shift to concomitant chemoradiation therapy.